Teacher Leadership Research in China (2020–2024): Trends, Gaps, and Future Directions in Educational Development - Wang Xianguo; Suraya Amirrudin (International Journal of Education and Humanities, 2025)
In 2020, China officially released the Recommendations of the Central Committee of the Communist Party of China on Formulating the 14th Five-Year Plan for National Economic and Social Development and the Long-Range Objectives for 2035, reaffirming the nation’s commitment to building a high-quality education system. This policy marks a new phase in China’s educational modernization, prompting deeper academic investigations into teacher leadership. However, despite its significance, research on teacher leadership in China still faces challenges regarding focus and implementation. This study aims to analyze the development of teacher leadership research in China from 2020 to 2024, a period characterized by the nation’s transition toward high-quality education. Using a systematic literature review methodology, this study identifies a fluctuating yet declining trend in publications on teacher leadership. Existing research predominantly focuses on theoretical exploration, conceptual clarification, and constructing theoretical frameworks, while empirical studies investigating practical applications remain scarce. Findings also indicate that studies on teacher leadership in higher education institutions, particularly within the framework of high-quality development, remain significantly underdeveloped. To address this gap, future research should integrate contemporary educational policies, expand the scope of inquiry, and diversify research themes. Strengthening the synergy between teacher leadership theory and practice is essential to supporting the construction of a high-quality education system in China